A disadvantaged childhood matters more if local unemployment is high - Wouter Zwysen (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Using multilevel models on the German Socio-Economic Panel Study this paper shows that disadvantaged young adults (16-35 years old) are more affected by the business cycle than their similarly educated counterparts from more advantaged backgrounds. We propose that a disadvantaged background lowers desirability on the labour market, which matters more to employers as the labour market tightens. When the local unemployment rate is high, young adults from a disadvantaged background are less likely to be hired for good jobs or hired at all than their more advantaged counterparts. These results are robust to different operationalisations and sibling fixed effects.
Keywords: 330; labour; family and networks; income and poverty